2021
DOI: 10.12998/wjcc.v9.i23.6734
|View full text |Cite
|
Sign up to set email alerts
|

Increased morbidity and mortality of hepatocellular carcinoma patients in lower cost of living areas

Abstract: BACKGROUND The incidence and mortality rates of hepatocellular carcinoma (HCC) are increasing in the United States. However, the increases in different racial and socioeconomic groups have not been homogeneous. Access to healthcare based on socioeconomic status and cost of living index (COLI), especially in HCC management, is under characterized. AIM The aim was to investigate the relationship between the COLI and tumor characteristics, treatment modalities, and surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Because of its characteristics of rapid tumor progression, recurrence, metastasis, and resistance to treatment, its prognosis is usually very poor. HCC, as a leading cause of cancer-related mortality worldwide, has a significant influence on the quality of life of HCC and also incurs huge economic costs ( Jemal et al, 2011 ; Sempokuya et al, 2021 ). Although many recent efforts have been made to treat HCC, the long-term prognosis of HCC patients remains very poor.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its characteristics of rapid tumor progression, recurrence, metastasis, and resistance to treatment, its prognosis is usually very poor. HCC, as a leading cause of cancer-related mortality worldwide, has a significant influence on the quality of life of HCC and also incurs huge economic costs ( Jemal et al, 2011 ; Sempokuya et al, 2021 ). Although many recent efforts have been made to treat HCC, the long-term prognosis of HCC patients remains very poor.…”
Section: Discussionmentioning
confidence: 99%
“…COLI is a relative marker of living expenses compared to United States estimates, with values above 100 conferring higher than average costs of living. COLI has not been extensively studied in relation to LCS or lung nodule outcomes; however, prior studies in individuals with hepatocellular cancer found that those with lower COLI presented with more advanced cancers, while higher COLI was associated with improved survival [29]. We found a weak association between individuals from lower COLI areas and smaller nodules < 6 mm (OR 0.933, p 0.056), while higher COLI areas were weakly associated with nodules between 6-8 mm (PR 1.084, p 0.048), the signi cance of which is undetermined.…”
Section: Socioeconomic Status and Nodule Sizementioning
confidence: 99%
“…Race has also been shown to influence treatment recommendations, with Black patients less likely to be offered surgical resection for certain skull-base tumors [22]. Furthermore, excess cancer mortality has been reported in some U.S. minority groups across cancer types [23][24][25][26][27][28][29][30][31][32]. As an example, based on SEER analysis (2000-2017) the epidemiological profile of metastatic bladder cancer suggests Black females are more likely to die from this disease than any other group [33].…”
Section: Big Data and Real-world Datamentioning
confidence: 99%